4x-3y=12

Subtract 4x from both sides of the equation.

-3y=12-4x

Divide each term by -3 and simplify.

Divide each term in -3y=12-4x by -3.

-3y-3=12-3+-4x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=12-3+-4x-3

Divide y by 1.

y=12-3+-4x-3

y=12-3+-4x-3

Simplify each term.

Divide 12 by -3.

y=-4+-4x-3

Dividing two negative values results in a positive value.

y=-4+4×3

y=-4+4×3

y=-4+4×3

y=-4+4×3

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-4+4(0)3

Simplify -4+4(0)3.

Multiply 4 by 0.

y=-4+03

Divide 0 by 3.

y=-4+0

Add -4 and 0.

y=-4

y=-4

Use the x and y values to form the ordered pair.

(0,-4)

(0,-4)

Remove parentheses.

y=-4+4(1)3

Simplify -4+4(1)3.

Multiply 4 by 1.

y=-4+43

To write -4 as a fraction with a common denominator, multiply by 33.

y=-4⋅33+43

Combine -4 and 33.

y=-4⋅33+43

Combine the numerators over the common denominator.

y=-4⋅3+43

Simplify the numerator.

Multiply -4 by 3.

y=-12+43

Add -12 and 4.

y=-83

y=-83

Move the negative in front of the fraction.

y=-83

y=-83

Use the x and y values to form the ordered pair.

(1,-83)

(1,-83)

Remove parentheses.

y=-4+4(2)3

Simplify -4+4(2)3.

Multiply 4 by 2.

y=-4+83

To write -4 as a fraction with a common denominator, multiply by 33.

y=-4⋅33+83

Combine -4 and 33.

y=-4⋅33+83

Combine the numerators over the common denominator.

y=-4⋅3+83

Simplify the numerator.

Multiply -4 by 3.

y=-12+83

Add -12 and 8.

y=-43

y=-43

Move the negative in front of the fraction.

y=-43

y=-43

Use the x and y values to form the ordered pair.

(2,-43)

(2,-43)

These are three possible solutions to the equation.

(0,-4),(1,-83),(2,-43)

Find Three Ordered Pair Solutions 4x-3y=12